Design and Synthesis of Some Carbamazepine Derivatives Using Several Strategies - Lauro, Figueroa-Valverde; Francisco, Díaz-Cedillo; Marcela, Rosas-Nexticapa; Guadalupe, Maldonado- Velazquez; Elodia, García-Cervera; Eduardo, Pool-Gomez; Horacio, Jarquin-Barberena; Maria, Lopez-Ramos; Fernanda, Rodriguez-Hurtado; Marissa, Chan-Salvador (Letters in Organic Chemistry, 2015)
In this study, is reported a straightforward route is reported for the synthesis of a series of carbamazepine derivatives using some strategies. The first stage was achieved by the reaction of carbamazepine with thiourea in the presence of pyridine to form the compound 3-(5H-dibenzo[b,f]azepin-5-yl)-2,5-dihydro-1,2,4-thiadiazol-5-amine (3). After 3 was made reacting with chloroacetyl chloride using triethylamine as catalyst to synthesis of a propanamide derivative (4). The following stage a carboxamide derivative (5) was synthesized by the reaction of 4 with benzaldehyde in basic medium. The fourth stage was achieved by the reaction of carbamazepine with ethylenediamine in presence of formaldehyde to form a new carboxamide derivative (7). Then, the compound 7 was made reacting with 2-hydroxy-1-naphthaldehyde using boric acid as catalyst to synthesis of a carbamazepine derivative (8). Finally, 8 was made reacting with 3,5- dintrobenzoic acid in the presence of dimetyhyl sulfoxide at mild conditions to form a new carbamazepine derivative 9. The structure of the compounds obtained was confirmed by elemental analysis, spectroscopy and spectrometry data. The proposed method offers some advantages such as simple procedure, low cost, and ease of workup.
Keywords: boric acid